The impact of published guidance on trends in the pharmacological management of depression in children and adolescents- a whole population e-cohort data linkage study in Wales, UK - Amanda Marchant (Psychological Medicine, 2025)
Background: This study evaluated the impact of 2015/2016 prescribing guidance on antidepressant prescribing choices in children. Methods: A retrospective e-cohort study of whole population routine electronic healthcare records was conducted. Poisson regression was undertaken to explore trends over time for depression, antidepressant prescribing, indications and secondary care contacts. Time trend analysis was conducted to assess the impact of guidance. Results: A total of 643,322 primary care patients in Wales UK, aged 6-17 years from 2010-2019 contributed 3,215,584 person-years of follow-up. Adjusted incidence of depression more than doubled (IRR for 2019 = 2.8[2.5-3.2]) with similar trends seen for antidepressants. Fluoxetine was the most frequently prescribed first-line antidepressant. Citalopram comprised less than 5% of first prescriptions in younger children but 22.9% (95% CI 22.0-23.8; 95% CI 2533) in 16–17-year-olds. Approximately half of new antidepressant prescribing was associated with depression. Segmented regression analysis showed that prescriptions of ‘all’ antidepressants, Fluoxetine and Sertraline were increasing before the guidance. This upward trend flattened for both ‘all’ antidepressants and Fluoxetine and steepened for Sertraline. Citalopram prescribing was decreasing significantly pre guidance being issued with no significant change afterward. Conclusions: Targeted intervention is needed to address rising rates of depression in children. Practitioners are partially adhering to local and national guidance. The decision-making process behind prescribing choices is likely to be multi-factorial. Activities to support implementation of guidance should be adopted in relation to safety in prescribing of antidepressants in children including timely availability of talking therapies and specialist mental health services. Further research is needed to explore GPs' prescribing preferences.